New Generation Speech Aid for Stuttering People - ODYA, Piotr; CZYŻEWSKI, Andrzej (Archives of Acoustics, 2008)
Modern Digital Signal Processors (DSP) may have small dimensions and very low current consumption, but they are able to execute complex algorithms. In addition, they can be easily reprogrammed using a standard PC computer. Taking advantage of these processors, it was possible to build a device, which can be used either as a speech aid or a hearing aid, or both. The paper placed emphasis on issues related to the implementation of algorithms applicable to speech aids. For example, spectral compression or delaying the audio signal are often used for speech fluency improvement, thus they are shortly reviewed in the paper. Some additional algorithms which can improve the quality of the audio signal are also described. Clinical tests proved that the SDSA improves speech fluency. A detailed description of tests carried out and of their results is included in the paper.